Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-long.516
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Propaganda Techniques in Memes

Abstract: Propaganda can be defined as a form of communication that aims to influence the opinions or the actions of people towards a specific goal; this is achieved by means of well-defined rhetorical and psychological devices. Propaganda, in the form we know it today, can be dated back to the beginning of the 17th century. However, it is with the advent of the Internet and the social media that it has started to spread on a much larger scale than before, thus becoming major societal and political issue. Nowadays, a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Loaded Language Loaded language is another propaganda technique that utilizes emotiontriggering terms or phrases to influence audiences' opinions Dimitrov et al, 2021) Some generated examples for appeal to authority and loaded language are shown in Table 2. Upon collecting the training data for generating loaded language, we fine-tune another BART (Lewis et al, 2020) on this dataset.…”
Section: Propaganda Generationmentioning
confidence: 99%
“…Loaded Language Loaded language is another propaganda technique that utilizes emotiontriggering terms or phrases to influence audiences' opinions Dimitrov et al, 2021) Some generated examples for appeal to authority and loaded language are shown in Table 2. Upon collecting the training data for generating loaded language, we fine-tune another BART (Lewis et al, 2020) on this dataset.…”
Section: Propaganda Generationmentioning
confidence: 99%
“…The rise in misconduct on social media is a prominent research topic. Some forms of online misconduct include rumours (Zhou et al, 2019), fake news (Aldwairi and Alwahedi, 2018;Shu et al, 2017;Nguyen et al, 2020), misinformation (Ribeiro et al, 2021;Shaar et al, 2022), disinformation (Alam et al, 2021;Hardalov et al, 2022), hate speech (MacAvaney et al, 2019;Zhang and Luo, 2019;Zampieri et al, 2020), trolling (Cook et al, 2018), and cyber-bullying (Kowalski et al, 2014;. Some notable work in this direction includes stance (Graells-Garrido et al, 2020) and rumour veracity prediction, in a multi-task learning framework (Kumar and Carley, 2019), wherein the authors proposed a Tree LSTM for characterizing online conversations.…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al (2021) argued that online attention can be garnered immensely via fauxtography, which could eventually evolve towards turning into memes that potentially go viral. To support research on these topics, several datasets for offensiveness, hate speech, and harmfulness detection have been created (Suryawanshi et al, 2020;Kiela et al, 2020;Pramanick et al, 2021a,b;Gomez et al, 2020;Dimitrov et al, 2021;Sharma et al, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…Reis et al ( 2020) built a dataset of memes related to the 2018 and the 2019 election in Brazil (34k images, 17k users) and India (810k images, 63k users) with focus on misinformation. Another dataset of 950 memes targeted the propaganda techniques used in memes (Dimitrov et al, 2021a), which was also featured as a shared that at SemEval-2021 (Dimitrov et al, 2021b). Leskovec et al (2009) introduced a dataset of 96 million memes collected from various links and blog posts between August 2008 and April 2009 for tracking the most frequently appearing stories, phrases, and information.…”
Section: Related Workmentioning
confidence: 99%